LANGUAGE FUNCTIONS USED IN MANUSIA SETENGAH SALMON BOOK BY RADITYA DIKA - ARISANDY, MADE DESSY (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Discourse analysis, language function, Manusia Setengah Salmonbook.This study investigates language functions used in Manusia Setengah Salmon book by Raditya Dika. The objectives of the study are to find the kinds of language function used by the author in the book and to describe the most dominant kinds of language functions found.This study uses descriptive qualitative approach. It is categorized as discourse analysis because this study analyzes the used of language in humor book genre. The data are collected from three short stories of nineteen stories which are related to the whole story and those are analyzed by using Roman Jakobson theory on language functions.The result of this study shows that there are several language functions used by the character in the book, including the author. They are; referential function, emotive function, conative function, metalingual function, phatic function, and poetic function. Referential function is the most dominant kind of language function used by Raditya Dika. This function is used in describing of Raditya Dika experience of his life in the book with thirty four sentences used.Then, the effective of language functions found in the book are, referential function, emotive function, and phatic function while conative function, metalingual function, and poetic function are rarely used in the book. Since this study is only analyzing the kinds and most dominant of language function used, it is more interesting to associate it with others theories such as sociolinguistics, psycholinguistics, drama or other theories that contains on the data are chosen. Besides, the researcher suggested next researcher to start further researches in any humor book genre or another phenomenon of language by using the other theory on language functions.